Advocating for Patients With Inflammatory Bowel Disease: How to Navigate the Prior Authorization Process. Issue 10 (8th February 2019) - Bhat, Shubha; Zahorian, Toni; Robert, Regine; Farraye, Francis A
Abstract: In an effort to manage health care costs and avoid improper medication use, prior authorizations (PAs) have become a standard stipulation required by payers in the determination of medication coverage. For gastroenterologists managing patients, especially those with inflammatory bowel disease (IBD), the PA process is time-consuming and further complicated by 2 additional factors: step therapy requirements and failure of payers to recognize updated IBD treatment pathways. These factors often lead to PA denials and cause treatment delays, which in turn can lead to disease progression, ongoing patient suffering, and ultimately an increase in both direct and indirect total costs. In this manuscript, the PA process, PA models, tips and available resources to navigate the PA process, and future advocacy efforts are discussed with the intent to help gastroenterology practices optimize PA outcomes and improve the care provided to patients with IBD and other gastrointestinal disorders. Abstract : Prior authorizations (PA) for inflammatory bowel disease treatment is time-consuming and complicated. Tip and available resources to navigate the PA process within gastroenterology practices to optimize PA outcomes and improve care provided to patients are discussed.